2013
DOI: 10.1248/cpb.c12-00820
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Pharmacological Activity of Alkaloids from Embryo of Lotus, <i>Nelumbo nucifera</i>

Abstract: Bisbenzylisoquinoline alkaloid, nelumboferine which was recently isolated from the embryo of Nelumbo nucifera, and stereoisomers of neferine, which is a major alkaloid of the embryo of N. nucifera, were stereo selectively synthesized. Pharmacological activity of nelumboferine, stereoisomers of neferine, liensinine, iso liensinine, and Omethylneferine were evaluated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
30
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 42 publications
(31 citation statements)
references
References 13 publications
1
30
0
Order By: Relevance
“…Liensinine showed significant antidepressant effects at lower doses than those of isoliensinine and neferine. Our previous report demonstrated that liensinine and isoliensinine decreased locomotor activity over 30 min but did not increase general activity [11]. Therefore, it is unlikely that liensinine and isoliensinine elicit anti‐immobility effects by enhancing locomotor activity.…”
Section: Discussionmentioning
confidence: 92%
See 3 more Smart Citations
“…Liensinine showed significant antidepressant effects at lower doses than those of isoliensinine and neferine. Our previous report demonstrated that liensinine and isoliensinine decreased locomotor activity over 30 min but did not increase general activity [11]. Therefore, it is unlikely that liensinine and isoliensinine elicit anti‐immobility effects by enhancing locomotor activity.…”
Section: Discussionmentioning
confidence: 92%
“…Figure shows the effects of liensinine, isoliensinine, neferine and imipramine on the time of immobility of mice. Anti‐immobility effects of liensinine, isoliensinine and neferine were examined 30 min after administration based on previous studies on its sedative effects and anxiolytic effects of neferine [7,11]. Liensinine elicited apparent antidepressant‐like effects at 10, 25 and 50 mg/kg.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…However, evidence of P-gp-facilitated neferine transport has not been shown in cell models. To our knowledge, researchers have focused on the synthesis and metabolism of isoliensinine (Zhou et al, 2012;Nishimura et al, 2013), but the interaction between isoliensinine and ABC transporters remains unclear. This prompted us to investigate and identify the relevant ABC transporters involved in regulation of the cellular levels of liensinine and its analogs.…”
Section: Introductionmentioning
confidence: 99%